2012
DOI: 10.1051/0004-6361/201219094
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing magnetic structures by present and future radio telescopes with Faraday rotation measure synthesis

Abstract: Context. Modern radio telescopes allow us to record a large number of spectral channels. The application of a Fourier transform to spectropolarimetric data in radio continuum, Faraday rotation measure (RM) synthesis, yields the "Faraday spectrum", which hosts valuable information about the magneto-ionic medium along the line of sight. Aims. We investigate whether the method of wavelet-based RM synthesis can help us to identify structures of regular and turbulent magnetic fields in extended magnetized objects, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 29 publications
(52 reference statements)
1
57
0
Order By: Relevance
“…The latter part, however, often turns out to be complicated, mainly because of the turbulent component of the magnetic field; it causes the relation between the Faraday depth and the physical depth to be non-trivial and produces the Faraday forest (Frick et al 2011;Beck et al 2012), many smallscale features, in F(f). Our previous work showed that F(f) calculated with a realistic model for the Milky Way (Akahori et al 2013) has the Faraday forest superposed on the large-scale diffuse emission.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter part, however, often turns out to be complicated, mainly because of the turbulent component of the magnetic field; it causes the relation between the Faraday depth and the physical depth to be non-trivial and produces the Faraday forest (Frick et al 2011;Beck et al 2012), many smallscale features, in F(f). Our previous work showed that F(f) calculated with a realistic model for the Milky Way (Akahori et al 2013) has the Faraday forest superposed on the large-scale diffuse emission.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…While it would be straightforward to estimate, for instance, the number of sources of synchrotron radiation and their Faraday depths, the Faraday spectrum could be used to obtain more information. The properties of F(f) were previously studied (e.g., Bell et al 2011;Frick et al 2011;Beck et al 2012;Ideguchi et al 2014). For instance, the characteristic features in F(f) caused by various configurations of the large-scale LOS magnetic field such as field reversal were examined using simple models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we now realise that even quite simple scenarios (e.g., a source consisting of two spatially unresolved polarised components, each with different RMs) can produce an apparent linear relationship between θ and λ 2 , but corresponding to a spurious value of RM; only when one considers the fractional polarisation, Π ≡ (Q 2 +U 2 )/I, as a function of λ 2 does the observer realise that something is amiss (Farnsworth et al 2011). In such cases, and also in sources for which there is no linear dependence of θ on λ 2 , we also now better appreciate the various ways in which q ≡ Q/I, u ≡ U/I and Π, all as a function of λ 2 , can provide detailed information on magnetic fields, ionised gas and turbulence (Bell et al 2011;Farnsworth et al 2011;Beck et al 2012;Bernet et al 2012;Farnes et al 2014a;Brandenburg & Stepanov 2014;Horellou & Fletcher 2014). Furthermore, it is now clear that over a fractional bandwidth of 25% as assumed by , there are considerable degeneracies as to the nature of the observed Faraday rotation (Law et al 2011;O'Sullivan et al 2012).…”
Section: Beyond the Rotation Measure Gridmentioning
confidence: 99%
“…Other techniques for identifying magnetic field structures from RM synthesis observations continue to be developed (e.g. Beck et al 2012).…”
Section: The Magnetic Skymentioning
confidence: 99%